Heating of charged particles at Thomson scattering of a monochromatic electromagnetic wave - Ognivenko, V.V. (Вопросы атомной науки и техники, 2007)
Plane monochromatic electromagnetic wave scattering by charged particles is investigated theoretically taking into account the influence of scattered incoherent electromagnetic radiation on particles motion. The spread in the particles-velocity due to interaction of particles with each other via the fields of spontaneous incoherent radiation is shown to appear in the process of scattering of incident wave.